Synoptic Analysis of a Heavy Rainfall Event over Southeast Region of Bangladesh Using WRF Model - Ahasan, M. N.; Mannan, M. A.; Debsarma, S. K. (Journal of Scientific Research, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–> Synoptic analysis of the heavy rainfall event of 7 September 2011 was carried out using the Weather Research and Forecasting (WRF) Model. This extraordinary rainfall event was localized over the southeast region of Bangladesh and recorded rainfall was 331 mm at Chittagong and 226 mm at Sandwip within a span of 24-h. The model was run at 9 km horizontal resolution using KF CPS with YSU PBL scheme. The model performance was evaluated by examining the different predicted parameters like mean sea level pressure, upper and lower level circulations, wind shear, relative vorticity, convergence, moisture and rainfall. The rainfall was validated with TRMM 3B42RT and observed rainfall data. The results indicate that the WRF model was able to simulate the heavy rainfall event, and associated synoptic features reasonably well, though there are some biases in the rainfall pattern. The results suggest that the highly localized heavy rain over southeast Bangladesh was the result of an interaction of the large scale monsoon system with cyclonic disturbances and required moisture have been supplied from the Bay of Bengal. The low level flow facilitated strong convergence over the region due to horizontal wind shear, which resulted in maintenance of the storms. Keywords: Heavy Rainfall; WRF Model; Simulation; Validation; TRMM. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i3.13171 J. Sci. Res. 5 (3), 421-434 (2013) <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–>